Paleocene planktonic foraminifera from DSDP Site 356, South Atlantic: paleoceanographic inferences - Krahl, Guilherme; Koutsoukos, Eduardo A. M.; Fauth, Gerson (Marine micropaleontology, 2017)
In the present study, the planktonic foraminiferal distribution in a core section representing an interval between the Cretaceous/Paleogene (K/Pg) boundary and the end of the Paleocene (Danian/Selandian) from DSDP Site 356 (São Paulo Plateau, South Atlantic) was analyzed. The results point towards a gradual recovery of the marine pelagic ecosystem in the aftermath of the K/Pg mass-extinction event. The changes in distribution patterns and composition of the Danian planktonic foraminiferal assemblages are primarily related to the instability and changing conditions of oceanic surface waters. The quantitative analyses of the planktonic foraminifera showed that a series of speciation events took place in the Danian immediately after the K/Pg boundary, marking three distinct main intervals: (i) in the Pα zone, evidenced by the predominance of specimens that likely inhabited the most superficial portions of the water column (mixed layer), represented mainly by microperforated taxa (Globoconusa, Guembelitria, Parvularugoglobigerina and Woodringina). The occurrence of this group suggests poorly stratified water masses and a water column with meso-eutrophic conditions. In this interval, the first appearance of spines in the planktonic foraminifera (Eoglobigerina, of the family Globigerinidae) evidences the development of a carnivorous habit; (ii) between zones P1a and P2 there is a continuous increase of species that inhabited the lower portion of the water column, in the thermocline and sub-thermocline, suggesting the recovery of the pelagic ecosystem with the development of a more stratified water column in mesotrophic to oligotrophic conditions; (iii) from zone P3 onwards, most of the planktonic foraminifera inhabited the lowest portions of the water column, together with the first occurrences of mixed-layer endosymbiont-bearing species such as Morozovella, Acarinina and Igorina.